Scheduling challenges within maintenance repair and overhaul operations in the civil aviation sector - Albakkoush, Salah Muftah M.; Pagone, Emanuele; Salonitis, Konstantinos (SSRN, 2020)
Aircraft Maintenance Repair and Overhaul (MRO) corporations provide two types of service: light and heavy maintenance. Typical MRO problems are related to scheduled and unscheduled aircraft maintenance because of the large number of components and parts that need a lead-in time for delivery and the consequent scheduling of work. This paper focuses on the significant causes of such problems affecting MRO operations. It addresses three major factors as follows: OEMs, Maintenance schedule and manpower and turnaround time. By a systematic review and analysis of scientific literature sources, it is shown that aviation industry standards do not permit aircraft to be scheduled unless they are maintained according to and comply with the stringent standards related to airworthiness. What seems to be important is effective maintenance schedule planning since this reduces time and cost, and enables aircraft to be maintained in a short time. Unfortunately, light maintenance remains beyond the control of airlines because no time allowance is programmed into flight schedules for such events vs increase the number of flight schedule per day
Keywords: Turnaroud time; Manpower; OEMs; Maintenance schedule